Quenched topological boundary modes can persist in a trivial system - Ching Hua Lee (Nature Portfolio, 2021)
Floquet topological engineering describes the driving of a topologically trivial system into transitory non-trivial state and there are many open questions about the underlying mechanisms. Here, the authors theoretically investigate the time evolution of a topological mode when the bulk band structure is driven into a topologically trivial structure, and show that it can survive unexpectedly long in a "frozen” regime, before gradually disappearing in the "melting” regime.